SHAKARIM AND EXPEDITIONS TO THE KAZAKH LAND: THE PROBLEM OF LITERARY DISCOURSE AND NATIONAL REPRESENTATION (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
The article considers the personality of Shakarim Kudaiberdiuly from the perspective of literary studies in the context of scientific expeditions to the Kazakh lands in the 20s and 30s of the 20th century. The objects of research were the expeditionary records of F.A. Fielstrup, M. Kuchinsky and other researchers, as well as Shakarim's works of historical and ethnographic content. The purpose of the work is to identify the discourse connection between expedition texts and Shakarim's works, analyze the textual representation of national identity and determine the role of the author's position in the formation of cultural memory. The methods of historical and comparative, intertextual analysis, discourse interpretation and the theory of cultural memory were used in the research. As a result, it was proven that Shakarim was not just an informant for the members of the expedition Nurkadyrov , but an intellectual figure who systematically explained the traditional worldview, customs and historical experience of Kazakh society. While the expedition materials describe the Kazakh economic system, social structure, family customs, and hunting culture, in Shakarim's works these phenomena are presented with artistic interpretation at the level of a national-spiritual concept. The intersection of these two different textual layers demonstrates the connection between the external scientific discourse and the internal literary discourse of national culture. The results of the study determine the scientific significance of considering Kazakh literature in conjunction with ethnographic sources and substantiate the relevance of studying Shakarim's heritage from a cultural-anthropological perspective.